An Ethnography of the Goodman Building The Longest Rent Strike - Caldararo, Niccolo (Palgrave Studies in Urban Anthropology,, 2019)
Through in-depth analysis and narrative investigation of an actual building occupation, Niccolo Caldararo seeks to not only offer an historical account of the Goodman Building in San Francisco, but also focus on the active resistance tactics of its residents from the 1960s to the 1980s. Taking as its focal point the building itself, the volume weaves in and out of every life involved and the struggles that surround it-San Francisco's urban renewal, ethnic clearing, gentrification, and municipal governance at a time of booming urban growth. Caldararo, a tenant at the center of its strikes and activities, provides a unique perspective that counteracts current trends in ethnographies of urban movements by grounding its analysis in physical and tangible space.